2011
DOI: 10.1159/000322601
|View full text |Cite
|
Sign up to set email alerts
|

Angiopoietin-Like 4 <i>(ANGPTL4)</i> Gene Polymorphisms and Risk of Brain Arteriovenous Malformations

Abstract: Background: Brain arteriovenous malformations (BAVM) are high-flow vascular lesions prone to intracranial hemorrhage (ICH). Abnormal angiogenesis is a key characteristic of BAVM tissue. Angiopoietin-like 4 (ANGPTL4), a secreted glycoprotein, is thought to be involved in angiogenesis and required for proper postnatal blood vessel partitioning. We investigated whether common single nucleotide polymorphisms (SNPs) in ANGPTL4 were associated with risk of BAVM or ICH. Methods and Results: We conducted a case-contro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
25
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 42 publications
(25 citation statements)
references
References 110 publications
0
25
0
Order By: Relevance
“…The vast majority of the studies that have so far investigated the genetic base of sporadic BAVMs have focused on SNPs of genes involved in angiogenesis and inflammation [14,15,16]. However, most of these studies have provided controversial and inconsistent results and a recent meta-analysis carried out by our research team has demonstrated a statistically significant association with BAVMs only for the IVS3-35A>G polymorphism of the ALK1 gene (ACVRL1) [14], consistent with the notion that ACVRL1 mutations are involved in the formation of arteriovenous dysplasia in patients with hereditary hemorrhagic telangiectasia [17].…”
Section: Discussionmentioning
confidence: 99%
“…The vast majority of the studies that have so far investigated the genetic base of sporadic BAVMs have focused on SNPs of genes involved in angiogenesis and inflammation [14,15,16]. However, most of these studies have provided controversial and inconsistent results and a recent meta-analysis carried out by our research team has demonstrated a statistically significant association with BAVMs only for the IVS3-35A>G polymorphism of the ALK1 gene (ACVRL1) [14], consistent with the notion that ACVRL1 mutations are involved in the formation of arteriovenous dysplasia in patients with hereditary hemorrhagic telangiectasia [17].…”
Section: Discussionmentioning
confidence: 99%
“…37 Some specific molecules affected by SNPs are TGF-b, an extracellular glycosylated protein that suppresses the effects of interleukins and is critical in de novo AVM formation; 32 brain-derived neurotrophic factor (BDNF), a protein that supports survival, development, and function of neurons; 55 interleukin-6 (IL-6), which contributes to vascular wall instability by stimulating the release of MMP; 32,33,38 and angiopoietin-like 4 (ANGPTL4), a glycoprotein believed to be involved in angiogenesis (Table 1). 31 Vascular endothelial growth factor is a critical signaling molecule that regulates angiogenesis and is typically suppressed in normal adult vasculature. VEGF has a potent mitotic effect and is highly expressed in children with recurrent AVMs.…”
Section: Avm Formationmentioning
confidence: 99%
“…The ANGPTL4 protein has been suggested to have a proangiogenic as well as an antiangiogenic effect 9 20. Suppression of angiogenesis may occur via the Raf/MEK/ERK1/2 MAP kinase pathway in endothelial cells 9 20.…”
Section: Discussionmentioning
confidence: 99%
“…Suppression of angiogenesis may occur via the Raf/MEK/ERK1/2 MAP kinase pathway in endothelial cells 9 20. Recent evidence from studies in knock-out mice showed that ANGPTL4 deficiency resulted in dysfunctional angiogenesis in retinal vessels and increased vessel permeability because of improper maturation 21.…”
Section: Discussionmentioning
confidence: 99%